Propostas para melhoria do desempenho acadêmico dos estudantes-trabalhadores dos cursos de graduação presencial - Nogueira, Livia de Souza (2019)
The objective of this study is to present proposals for improving the academic performance of student-workers at Universidade Federal do Espírito Santo in order to improve the success rate of this institution. The study consists on verifying the academic levels for performance, for retention and for dropout of student-workers and non-workers of the morning courses in Administration, Economic Sciences and Law at UFES. In addition, it was proposed to indicate actions to improve the performance of student-workers in the University. The research methodology is classified as exploratory and explanatory in a quali-quanti approach. In addition to the bibliographic survey, we used data from institutional reports from UFES, from other Brazilian Federal Universities, interviews with course coordinators, and the application of a questionnaire to UFES classroom teachers. The analysis of the results showed that the student-workers presented unsatisfactory performance compared to the non-workers, as well as higher levels of retention and dropout. We conclude this study by presenting an Institutional Intervention Proposal composed of eleven actions aimed at improving the student success rate of students-workers within the Federal University of Espirito Santo.